CeO2 foam-like nanostructure: biosynthesis and their efficient removal of hazardous dye - Alinaghi Langari, Aliakbar; Soltaninezhad, Simin; Zafarnia, Niloofar; Heidari, Mohammadreza; Varma, Rajender S; Ebrahimi, Zahra; Azhdari, Sara; Borhani, Fariba; Khatami, Mehrdad (Bioprocess and biosystems engineering, 2021)
In this study, CeO2 (cerium oxide) nanoparticles were synthesized using Pinus halepensis pollen and were characterized by field emission scanning electron microscopy (FESEM), powder X-ray diffraction (PXRD) and Raman spectroscopy. The results showed that the ensuing CeO2 nanostructures, ranging in size from 5 to 25 nm, had high porosity. Synthesized CeO2 showed the effective catalytic activity towards the photocatalytic removal of dyes. In this work, the photocatalytic activity to removal dye (methyl violet 2B), in the absence of UV radiation, using cerium dioxide nanoparticles (CeO2-NP) was determined. In this research, four main factors such as effect on color, concentration and pH were examined and maximum %R was obtained about was 97% in 75 min in presence of 50 mg of hydrogen peroxide.
Keywords: nanostruktury; poréznost; Porosity; Cerium; Coloring Agents; Nanostructures; Pinus; borovice; barvicí látky; cer